Answer:
x = - 1
Step-by-step explanation:
3(x + 1) = - 2(x - 1) - 4 ← distribute parenthesis on both sides
3x + 3 = - 2x + 2 - 4
3x + 3 = - 2x - 2 ( add 2x to both sides )
5x + 3 = - 2 ( subtract 3 from both sides )
5x = - 5 ( divide both sides by 5 )
x = - 1
Answer:
y=2x+17
Step-by-step explanation:
y-y1=m(x-x1)
y-1=2(x-(-8))
y-1=2(x+8)
y=2x+16+1
y=2x+17
Answer:
$495.84
Step-by-step explanation:
1,036.89-495.05= 541.84- 46= 495.84
<span>arithmetic sequence<span>a sequence in which each term is found by adding the same number to the previous term</span></span>